2020
DOI: 10.3390/nu12051326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intensive Lifestyle Treatment (Diet Plus Exercise) on Endothelial and Vascular Function, Arterial Stiffness and Blood Pressure in Stage 1 Hypertension: Results of the HINTreat Randomized Controlled Trial

Abstract: Lifestyle modification is an important component of essential hypertension (EH) therapy. The aim of the Hypertension Intensive Nutrition Treatment (HINTreat) parallel, randomized controlled trial was to examine the effect of a 6-month intensive lifestyle treatment (ILT) (diet plus exercise with monthly visits) compared to the usual care. A total of 76 adults with stage 1 EH were randomized (38 in each group). Dietary analysis, anthropometry, physical activity, biochemical and urine profile, blood pressure (BP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 87 publications
(102 reference statements)
1
17
0
Order By: Relevance
“…The majority of controlled lifestyle (including diet and/or exercise) interventions have failed to demonstrate a clear effect on ccIMT compared to control (24,49), while only one of these unsuccessful studies reported a subgroup analysis with highrisk participants (50). However, some controlled trials using diet and/or exercise have been able to show a favourable effect on ccIMT (decrease or slowed progression), and when dietary recommendations were given, these included advice to adhere to a traditional Mediterranean diet (which is a plant-based dietary pattern) (51,52) or to consume less salt and alcohol and more fruit and vegetables (53), and in one study, more dairy (20) (all randomized controlled trials).…”
Section: Comparison With Results From the Literaturementioning
confidence: 99%
“…The majority of controlled lifestyle (including diet and/or exercise) interventions have failed to demonstrate a clear effect on ccIMT compared to control (24,49), while only one of these unsuccessful studies reported a subgroup analysis with highrisk participants (50). However, some controlled trials using diet and/or exercise have been able to show a favourable effect on ccIMT (decrease or slowed progression), and when dietary recommendations were given, these included advice to adhere to a traditional Mediterranean diet (which is a plant-based dietary pattern) (51,52) or to consume less salt and alcohol and more fruit and vegetables (53), and in one study, more dairy (20) (all randomized controlled trials).…”
Section: Comparison With Results From the Literaturementioning
confidence: 99%
“…1 Clinical and preclinical observations suggest that a large number of concomitant modifiable cardiovascular risk factors determine the manifestation and progression of AF. 2 Interestingly, most AF risk factors such as coronary artery disease, 3 heart failure, 4 hypertension, 5 diabetes, and obesity 6 are linked to dietary intake and lifestyle components.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a small number of controlled trials have assessed the effect of a combined lifestyle intervention (including diet and other lifestyle factors) on ccIMT (22,(24)(25)(26)(27)(28) , and only two of these trials were conducted with generally healthy participants (27,28) : in a suburban population in Japan, Okada et al observed no significant effect of a 2-year lifestyle modification on mean ccIMT change (compared to control; dietary recommendations were based on the goals of the National Cholesterol Education Program; <30 % total fat, <7 % saturated fat and <200 mg dietary cholesterol per day) (27) . Similarly, in a study with perimenopausal women in the United States, Wildman et al observed no significant effect of a 4-year diet (≤25 % total fat, ≤7 % saturated fat, ≤100 mg dietary cholesterol and 1300 kcal/d) and exercise intervention on mean ccIMT change (compared to control) (28) .…”
Section: Discussionmentioning
confidence: 99%